CHARACTER EDUCATION IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC: indonesia - Ruly Nadian Sari; Wiwin Windayanti; Maya Aulia (Jurnal Pendidikan Guru Madrasah Ibtidaiyah AL-IBDA', 2021)
Abstract Strengthening character education plays an important role in shaping the character of students. A great nation is a nation that has a strong human resource character side by side with superior competence. Character education is a process of applying moral and religious values ​​to students through science, the application of these values ​​to oneself, family, fellow friends, educators and the surrounding environment as well as God Almighty. The presence of the media in the world of education, especially in the context of teaching effectiveness and efficiency is very much needed. The development of the social character of elementary school-aged children has increased, from initially only socializing with family at home, then gradually getting to know the people around them. Keywords: Character Education; Daring learning; Covid 19